Additive Engineering by Bifunctional Guanidine Sulfamate for Highly Efficient and Stable Perovskites Solar Cells. Issue 47 (2nd November 2020) - Liu, Xuping; Wu, Jihuai; Yang, Yuqian; Wang, Deng; Li, Guodong; Wang, Xiaobing; Sun, Weihai; Wei, Yuelin; Huang, Yunfang; Huang, Miaoliang; Fan, Leqing; Lan, Zhang; et al.
Abstract: High efficiency and good stability are the challenges for perovskite solar cells (PSCs) toward commercialization. However, the intrinsic high defect density and internal nonradiative recombination of perovskite (PVK) limit its development. In this work, a facile additive strategy is devised by introducing bifunctional guanidine sulfamate (GuaSM; CH6 N3 +, Gua + ; H2 N−SO3 −, SM − ) into PVK. The size of Gua + ion is suitable with Pb(BrI)2 cavity relatively, so it can participate in the formation of low‐dimensional PVK when mixed with Pb(BrI)2 . The O and N atoms of SM − can coordinate with Pb 2+ . The synergistic effect of the anions and cations effectively reduces the trap density and the recombination in PVK, so that it can improve the efficiency and stability of PSCs. At an optimal concentration of GuaSM (2 mol%), the PSC presents a champion power conversion efficiency of 21.66% and a remarkably improved stability and hysteresis. The results provide a novel strategy for highly efficient and stable PSCs by bifunctional additive. Abstract : A facile and effective additive strategy is devised by introducing bifunctional guanidine sulfamate (GuaSM) molecules into perovskite (PVK) layer. The synergistic effect of the SM − anions and the Gua + cations are demonstrated, which effectively reduces the trap density and the recombination in PVK, so that the photovoltaic performance and stability of the perovskite solar cells are improved noticeably.